Financial Analysis of Green Petroleum Coke as A Coal Blend in Steel Industry to Support National Energy Security - Naimah, Khoirun; Sasongko, Nugroho Adi; Widayatno, Rudy Laksmono (Universitas Airlangga, 2021)
Green Petroleum Coke (GPC), produced by Pertamina RU II Dumai, is the product of refined petroleum, which still has good quality but has not been utilized to its full potential. Such as Sulfur 0.5%; FC 86.03%; Ash 0.10%; VM 13.82%; Moist 10, 52%; and the calorific value of 7500 kcal/kg. Therefore, one effort that can do is diversification, namely the use of GPC as a mixture of other fuels (fossil) to increase the selling value of GPC. This diversification is also in line with the national energy policy in PP. 79/2014 that the program aims to increase the availability of national energy sources. This study aims to determine the feasibility of using GPC as a coal mixture in Industry (Krakatau Steel) with an overview of economic aspects. Data obtained by qualitative methods consisting of interviews, observation, and documentation. Based on the research results from 2 scenarios, both scenario 1 (GPC 4%) and scenario 2 (GPC 18%), it is found that the NPV is positive, IRR is above the discount rate, and BCR> 1. Thus, the use of GPC as a coal mixture is considered feasible to run and can support national energy security. Keywords: Diversification, Feasibility, Petroleum Coke, Investment DecisionJEL: G11, G32